2011
DOI: 10.1111/j.1525-1446.2011.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Status in Adults with Depression in the National Health and Nutrition Examination Survey, 2005–2006

Abstract: Although depressed adults were less active than nondepressed adults, their physical activity levels were close to the recommended guidelines. Public education regarding efficacy of physical activity and encouragement of appropriate activity levels could contribute to prevention and treatment of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 33 publications
4
50
2
Order By: Relevance
“…In overweight/obese adults, a reduced risk of depression was associated with increasing moderate-to-vigorous-intensity physical activity and decreasing sedentary time (Vallance et al, 2011). Another study on data from over 4,000 men and women aged 20 years or more confirmed that adults with depression spent significantly less time both in light and moderate physical activity than non-depressed adults (Song et al, 2012). In a longitudinal study of over 9,000 people, regular physical activity was associated with a reduced likelihood of depressive symptoms at follow-up (Azevedo Da Silva et al, 2012).…”
Section: The Relationship Between Exercise and Depressionmentioning
confidence: 79%
“…In overweight/obese adults, a reduced risk of depression was associated with increasing moderate-to-vigorous-intensity physical activity and decreasing sedentary time (Vallance et al, 2011). Another study on data from over 4,000 men and women aged 20 years or more confirmed that adults with depression spent significantly less time both in light and moderate physical activity than non-depressed adults (Song et al, 2012). In a longitudinal study of over 9,000 people, regular physical activity was associated with a reduced likelihood of depressive symptoms at follow-up (Azevedo Da Silva et al, 2012).…”
Section: The Relationship Between Exercise and Depressionmentioning
confidence: 79%
“…Lower rates of physical activity and increased sedentary behaviours are also commonly observed in currently obese (Bailey et al, 2007, Tucker andTucker, 2011) and psychiatric patients (Azevedo Da Silva et al, 2012, Song et al, 2012 and are also risk factors for the future development of both these conditions. Rates of sleep disorders such as insomnia and sleep apnoea are also increased in obesity and psychiatric disorders (Costa M A N U S C R I P T…”
Section: Possible Mediators Of the Relationship Between Obesity And Pmentioning
confidence: 99%
“…There were no differences in sedentary and vigorous physical activity among groups. After controlling for socio-demographic factors, those at greater risk for depression were middle-aged women with self-reported poor health status with less moderate physical activity (Song, Lee, Baek, & Miller, 2012).…”
Section: Phq-9 Score ≤4 (No Depression)mentioning
confidence: 99%